The effect of sidewall friction on complex channel geometry using LABSWE / Firdaus Kamaruzaman and Siti Habibah Shafiai - Kamaruzaman, Firdaus; Shafiai, Siti Habibah (Penerbit UiTM (UiTM Press), 2013)
Lattice Boltzmann Model for Shallow Water Equation with Turbulence Modeling (LABSWETM) is used to study the flow patterns of sidewall friction effects. The lattice Boltzmann method (LBM) approach in recovery the macroscopic governing equation which is shallow water equation from the microscopic flow behavior of particle movement as described by kinetic theory is explored. With the solution of force term to be used in lattice Boltzmann equation, the boundary condition of LBM is explored. With the use of bed and wall friction coefficients, the importance of Manning’s coefficient in determining the outcome of flow patterns simulation is explained. For model verification, the model represents a straight channel with a circular cavity attached to it. The result of this simulation includes the water circulation patterns, cross-section of average velocity distribution, and water depth. For validation, the cross-sections of the model in term of velocity vectors are compared against alternative numerical and experimental data.